MUC4 is not expressed in cell lines used for live cell imaging [version 2; peer review: 2 approved] - Naouel Athmane (Wellcome, 2021)
Background: The ability to visualise specific mammalian gene loci in living cells is important for understanding the dynamic processes linked to transcription. However, some of the tools used to target mammalian genes for live cell imaging, such as dCas9, have been reported to themselves impede processes linked to transcription. The MUC4 gene is a popular target for live cell imaging studies due to the repetitive nature of sequences within some exons of this gene. Methods: We set out to compare the impact of dCas9 and TALE-based imaging tools on MUC4 expression, including in human cell lines previously reported as expressing MUC4. Results: We were unable to detect MUC4 mRNA in these cell lines. Moreover, analysis of publicly available data for histone modifications associated with transcription, and data for transcription itself, indicate that neither MUC4, nor any of the mucin gene family are significantly expressed in the cell lines where dCas9 targeting has been reported to repress MUC4 and MUC1 expression, or in the cell lines where dCas13 has been used to report MUC4 RNA detection in live cells. Conclusions: Methods for visualising specific gene loci and gene transcripts in live human cells are very challenging. Our data suggest that care should be given to the choice of the most appropriate cell lines for these analyses and that orthogonal methods of assaying gene expression be carefully compared.